ANALISIS PENILAIAN TAMU TENTANG PELAYANAN CONCIERGE PERSPEKTIF PELAYANAN KARYAWAN DIVISI CONCIERGE, DAN FEEDBACK TAMU SECARA UMUM (STUDI KASUS DI SINTESA PENINSULA HOTEL MANADO) - Hendri Reydi Bandil; Claurensya Maramis; Sonny Wijanarko (Jurnal Hospitaliti, 2022)
The purpose of this study is to first describe the guest's assessment of the concierge service at the Sintesa Peninsula Hotel Manado. Second, to identify guest feedback about services at concierge section of the Sintesa Peninsula Hotel Manado. The research location is at the Sintesa Peninsula Hotel Manado, precisely on Jl. Jendral Sudirman, Wenang Mountain, Pinesaan, Wenang, Manado City, North Sulawesi. There were three informants/guests interviewed by the researcher. There were three informants/concierge employees interviewed by the researcher. Researchers also retrieved data sources through Tripadvisor by taking twelve screenshots from April 2019 to April 2020. Researchers used various data sources, such as field notes, journals/diaries, and smartphones to record videos during interviews. The results showed that the concierge services as a whole was very good, but there were some guests who felt that this hotel did not match the stars clasification for the facilities were not good. There were also several guests who rated one of the employees as having poor service. However, the overall the service is very good. It is suggested that the hotel must pay more attention to some indicators of a five-star hotel, so that it can match the stars.